Storage management practices and mycotoxin contamination of sorghum (Sorghum bicolor) in northwest Ethiopia - Sadik, J.A.; Righetti, L.; Fentahun, N.; Brouwer, Inge D.; Tessema, M.; Abera, M.; van der Fels-Klerx, H.J. (Elsevier, 2025)
Mycotoxins are toxic metabolites produced by certain fungal species that affect animal and human health. Data on the relationships between specific traditional storage management practices of sorghum and mycotoxin contamination are rarely available in Ethiopia. The aim of this study was to investigate current sorghum storage management practices in major sorghum producer locations in Northwest Ethiopia and their relationships with mycotoxin contamination. Sorghum storage management practices of 120 farmers were surveyed, the occurrence of multiple mycotoxins in samples from their stored sorghum was determined, and potential relationships between the traditional storage management practices and mycotoxin contamination were analyzed. Samples were analyzed using UPLC-MS/MS for 33 different mycotoxins. About 88% of the samples were contaminated with at least one mycotoxin. The detected mycotoxins belong to one of the four mycotoxin categories, produced by Aspergillus spp, Fusarium spp, Penicillium spp, and Alternaria spp. From the total, 3%, 7%, and 3% of the samples were contaminated with aflatoxins, ochratoxin A, and zearalenone, respectively, above the EU regulatory limits. The measured concentrations that bypassed EU regulatory limits were 9.14, 18.34 and 29.13 (μg/kg) for total aflatoxins, 5.31, 12.50, 14.94, 15.77, 32.94, 56.81, 58.07 and 112.59 (μg/kg) for Ochratoxin A, and 123.48, 238.43 and 431.78 (μg/kg) for Zearalenone, respectively. Logistic regression showed relationships between the traditional storage management practices with mycotoxin contamination. The age and the experience of the Main Person Responsible for Storage management (MPRS), the placement of the storage structure, and the insecticide application showed negative relationships with multi-mycotoxin contamination. On the other hand, the educational status of the MPRS and the type of storage structure showed positive relationships with mycotoxin contamination. Therefore, it is recommended that farmers receive training in proper sorghum storage management to further reduce the mycotoxin contamination in the grain.